2001
DOI: 10.1073/pnas.251357198
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms underlying rapid experience-dependent plasticity in the human visual cortex

Abstract: Visual deprivation induces a rapid increase in visual cortex excitability that may result in better consolidation of spatial memory in animals and in lower visual recognition thresholds in humans. ␥-Aminobutyric acid (GABA)ergic, N-methyl-D-aspartate (NMDA), and cholinergic receptors are thought to be involved in visual cortex plasticity in animal studies. Here, we used a pharmacological approach and found that lorazepam (which enhances GABAA receptor function by acting as a positive allosteric modulator), dex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
49
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(55 citation statements)
references
References 53 publications
6
49
0
Order By: Relevance
“…This is also in line with the decrease of inhibition after full visual deprivation (blindfolding), measured by TMS, pharmacological manipulations and BOLD (38)(39)(40)(41). A decrease of GABA should affect not only overall neuronal excitability, but also neuronal selectivity, as both orientation and spatial frequency selectivity are mediated by GABAergic intra-cortical inhibitory circuitry (reviewed in42).…”
Section: Introductionsupporting
confidence: 73%
“…This is also in line with the decrease of inhibition after full visual deprivation (blindfolding), measured by TMS, pharmacological manipulations and BOLD (38)(39)(40)(41). A decrease of GABA should affect not only overall neuronal excitability, but also neuronal selectivity, as both orientation and spatial frequency selectivity are mediated by GABAergic intra-cortical inhibitory circuitry (reviewed in42).…”
Section: Introductionsupporting
confidence: 73%
“…For example, a study that recorded the activity of single V1 neurons in macaque monkeys demonstrated that SCO suppressed top-down attentional modulation of the primary visual cortex (Herrero et al, 2008). Furthermore, research by Boroojerdi and colleagues showed that experience-dependent plasticity in the human visual cortex was blocked with all the three agents (LZP, SCO, and DM; Boroojerdi et al, 2001). A combination of task and measurement differences between the reports and our experiments may have contributed to the conflicting results.…”
Section: Discussionmentioning
confidence: 99%
“…In each test session, a different drug was administered at a dosage selected to have mild psychogenic and sedating effects (Boroojerdi, Battaglia, Muellbacher, & Cohen, 2001). The following agents were used (within subjects): (i) DM (120 mg, 40 ml of Dampo syrup), a potent noncompetitive NMDA receptor antagonist (Wong, Coulter, Choi, & Prince, 1988); (ii) LZP (1.5 mg, pill), a short-acting benzodiazepine that at this dose produces functional potentiation in specifically the GABA A receptors (Sybirska et al, 1993); and (iii) SCO (1.5-mg dermal patch behind the ear), a muscarinic receptor antagonist (Frey et al, 1992).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been strongly implicated in synaptic plasticity and learning (Artola and Singer, 1987;Miller et al, 1989;Kirkwood et al, 1996). Both AMPA and NMDA glutamate receptors can be found in the visual cortex (Kumar et al, 1994;Rivadulla et al, 2001) and both play roles in synaptic potentiation (Bear, 1996;Rumpel et al, 1998;Quinlan et al, 1999;Boroojerdi et al, 2001;Watt et al, 2004). AMPA receptors are thought to contribute to information transmission between neurons, whereas NMDA receptors are mainly considered to be coincidence detectors that activate after multiple previous depolarizations (Malenka and Nicoll, 1999).…”
Section: Introductionmentioning
confidence: 99%